A Study on the Correlations of Anxiety and Depression With Self-Management Ability and Endogenous Creatinine Clearance Rate in Renal Transplant Recipients - Hu, ShiMin; Li, Yu; Quan, MingTao; Yang, ShuJuan; Wan, ZhaoMei; Yan, XiaoYong; Tan, ZhouKe; Liang, GuoBiao (Frontiers in Psychiatry, 2021)
Objective: To explore the effects of anxiety and depression on the self-management ability and endogenous creatinine clearance rate of renal transplant patients. Method: Eighty-eight renal transplant recipients who were followed up in the outpatient clinic of the Affiliated Hospital of Zunyi Medical University were selected using convenient sampling. The self-made general data sheet, Self-Rating Anxiety Scale, Self-Rating Depression Scale, and Self-Management Scale for Kidney Transplant Recipients were used. Correlation analysis was used to find factors related to endogenous creatinine clearance, while multiple linear regression was used to identify factors influencing endogenous creatinine clearance. Patients with or without anxiety and depression were divided into groups, and the indexes of the groups were compared using the independent samples t test, rank-sum test, or chi-squared test. Results: Anxiety was present in 12.5% of patients, depression in 25%, and a moderate level of self-management in 34.1%. The endogenous creatinine clearance rate was negatively correlated with age and degree of depression, and positively correlated with body mass index, treatment management score, and psychosocial management score. The main influencing factors of endogenous creatinine clearance rate were age, sex, depression, body mass index, and treatment management score. The endogenous creatinine clearance rate and psychosocial management ability were significantly higher in patients without anxiety and depression than in patients with anxiety and depression (all P < 0.05). Conclusions: Anxiety and depression showed significant negative effects on the psychosocial self-management ability and endogenous creatinine clearance rate of renal transplant recipients and thus should be given more attention.